THE ROLE OF COMPUTER-BASED LEARNING IN INCREASING INDONESIAN SKILLS AT COKROAMINOTO SUKARESMI HIGH SCHOOL - Santi Rusmayanti (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
This study aims to analyze the role of computer-based learning in improving Indonesian language skills at Cokroaminoto Sukaresmi Senior High School. Computer-based learning has become a significant trend in education, including language learning. This method offers various advantages, such as interactivity, accessibility, and flexibility of time and place. This research was conducted using a quantitative approach by distributing questionnaires to Cokroaminoto Sukaresmi SMA students who had attended a computer-based learning program for Indonesian. The collected data were analyzed statistically using descriptive techniques. The results of the study show that computer-based learning has a significant role in improving Indonesian language skills at Cokroaminoto Sukaresmi Senior High School. Students reported improvements in their abilities in various aspects of language such as vocabulary, grammar, reading comprehension, and writing skills. They also expressed high satisfaction with the use of this method in learning Indonesian. Computer-based learning at Cokroaminoto Sukaresmi Senior High School can provide an interesting and effective learning experience for students. With its interactive features, students can engage in interactive exercises, simulations and assignments designed to improve Indonesian language skills. In addition, the flexibility of time and place offered by computer-based learning allows students to study according to their individual needs and preferences. In conclusion, computer-based learning has a positive role in improving Indonesian language skills at Cokroaminoto Sukaresmi High School. This learning can provide an interactive, effective, and fun learning experience for students. Therefore, it is suggested that this approach should continue to be used and developed in the context of learning Indonesian in high school to optimize learning outcomes and prepare students to face increasingly complex global demands in today's digital era..